2018
DOI: 10.1177/1098612x18805862
|View full text |Cite
|
Sign up to set email alerts
|

Profibrotic effects of angiotensin II and transforming growth factor beta on feline kidney epithelial cells

Abstract: Objectives The aim of this study was to evaluate the role of angiotensin II (AT-II) and its main mediator, transforming growth factor beta 1 (TGF-β1), in the development of feline renal fibrosis. Methods Expression of marker genes indicating epithelial-to-mesenchymal transition (EMT), profibrotic mediators and matricellular proteins was measured in feline kidney epithelial cells (Crandell Rees feline kidney [CRFK] cells) after incubation with AT-II and/or TGF-β1. Results Cells incubated with TGF-β1 or the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Ang II-dependent connective tissue growth factors (CTGF) and transforming growth factor-β (TGF-β) are initial pro-fibrotic mediators involved in cardiac fibrosis ( Wong et al, 2018 ; van Beusekom and Zimmering, 2019 ). The expression of CTGF and TGF-β are interlinked.…”
Section: Angiotensin II Receptors and Signaling Pathwaysmentioning
confidence: 99%
“…Ang II-dependent connective tissue growth factors (CTGF) and transforming growth factor-β (TGF-β) are initial pro-fibrotic mediators involved in cardiac fibrosis ( Wong et al, 2018 ; van Beusekom and Zimmering, 2019 ). The expression of CTGF and TGF-β are interlinked.…”
Section: Angiotensin II Receptors and Signaling Pathwaysmentioning
confidence: 99%
“…Recently, CRFK cells have been reported to have the characteristics of fibroblast, particularly regarding morphology, biochemistry, and molecular biology, although CRFK cells have been established as an epithelial cell line [ 21 ]. Moreover, van Beusekom et al [ 31 ] reported that TGF-β1 changed the morphology of CRFK cells from an epithelial phenotype to a fibroblastic phenotype and that it significantly induced the expression of some EMT marker genes in CRFK cells, suggesting that CRFK cells can undergo EMT. In the present study, senescence appeared more important than apoptosis for growth suppression in irradiated CRFK cells.…”
Section: Discussionmentioning
confidence: 99%
“…As the kidney is a target organ of MMI-induced toxicity, an immortalized cell line derived from the renal cortex of a normal cat (CRFK) was used [ 25 ]. Although uncertainty has been suggested about the epithelial vs. mesenchymal phenotype of CRFK cells [ 26 ], they have been originally described as epithelial [ 25 ], and they are widely used accordingly [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%